Association of Baseline Sleep Quality With Trajectories of Depressive Symptoms in Patients Undergoing Interferon Treatment. Issue 8 (October 2015) - Marron, Megan M.; Anderson, Stewart J.; Garrity, Jessica; Reynolds, Charles F.; Lotrich, Francis E.
ABSTRACT: Objective: Some patients with hepatitis C starting interferon-α (IFN-α) therapy experience depression, although many patients do not develop depressive symptoms. We have found that poor sleep is associated with increased depressive symptoms on average. It is unknown whether this association holds generally or is driven by a specific, distinct subgroup. This investigation first determined whether patterns of change in depressive symptoms form clinically meaningful, distinct subgroups and then tested the extent to which sleep disturbances are associated with a less favorable depression trajectory. Method: Group-based trajectory modeling was used on 124 patients with hepatitis C who started IFN-α therapy. The Pittsburgh Sleep Quality Index (PSQI) assessed pretreatment sleep, the Beck Depression Inventory minus the sleep question assessed depression over time, and the Structured Clinical Interview for DSM-IV provided categorical diagnoses. Results: Three distinct subgroups were found, where each subgroup shared similar patterns of depressive symptoms over time. The groups were characterized as "nondepressed, " "slow increase, " and "rapid increase." The nondepressed subgroup (44.4%) experienced low depressive symptoms with little change over time. In comparison, all rapid increasers (11.3%) were diagnosed as having a mood disorder by 12 weeks of treatment. The PSQI was strongly associated with group membership, where the odds of developing a rapid increase was elevated 39% for every unit-score increase in the PSQI compared with individuals who remained nondepressed (odds ratio = 1.39, 95% confidence interval = 1.07–1.80, adjusted for depression at baseline). Conclusions: Only a distinct subpopulation of people is notably vulnerable to a developing a rapid increase in depression symptoms during IFN-α therapy. This group may be identifiable by their markedly poor sleep before IFN-α therapy.